An analysis of the current educational status and future training needs of China's rural doctors in 2011. Issue 1050 (6th February 2013) - Li, Xingming; Liu, Juyuan; Huang, Jianshi; Qian, Yunliang; Che, Lu
Abstract : Objectives: To analyse the educational status and future training needs of China's rural doctors and provide a basis to improve their future training. Methods: A cross-sectional epidemiological survey was used for the analysis, and 17 954 rural doctors chosen randomly from the eastern, central and western regions of China in 2009–2010 were surveyed to ascertain their average training time and the methods used for and content of their training. Results: In general, 8671/17 778 (48.77%) of respondents received less than 12 days of training in a year. Conference sessions seemed to be the major route of training, with 10 150/17 925 respondents (56.62%). Clinical skills, with a response rate of 14 441/17 926 (80.56%), seemed to be the most popular training content. With regard to the general needs for training time received, 6547/18 255 (35.86%) of respondents hoped the average training time received a year would be less than 12 days; on-site guidance from a senior doctor was the most popular training method with response rate of 10 109/17 976 (56.24%), and clinical skills was what rural doctors wished to study the most, with a positive response of 16 744/17 962 (93.22%). Statistically significant differences existed in the current status and training time, training method and training content needs of China's rural doctors. Conclusions: Our results suggest that the training status and needs of China's rural doctors are still disjointed; measures including the introduction of remote education and clinical further education, extended training time and more clinical skills training should be adopted.